Rubus coreanus extract prevents kidney fibrosis through TGF-β/Smad pathway inhibition - Wencheng Jin; Ara Cho; Bogyeong Cho; Nayeon Shin; Yun Kyu Oh; Chun Soo Lim; Jung Pyo Lee; Jeonghwan Lee (PLoS ONE, 2025)
Rubus coreanus has been found to have various health benefits including anti-oxidative effects. In this study, we aimed to investigate the efficacy of water-soluble extract of Rubus coreanus (MN705) in preventing kidney fibrosis in a mouse model of unilateral ureteral obstruction (UUO) and in an in vitro model of TGF-β-challenged HK-2 cells. Male C57BL/6 mice (7 weeks old) were randomly assigned to the sham/vehicle (distilled water), sham/MN705 (600 mg/kg/day), UUO/vehicle, UUO/MN705-low dose (300 mg/kg/day), and UUO/MN705-high dose (600 mg/kg/day) groups. After 7 days of pre-treatment, sham or UUO operation was performed, and treatment drugs were administered at the same dose for 7 days. In addition, HK-2 cells and human renal proximal tubular epithelial cells were cultured and challenged with TGF-β (2 ng/ml) with or without an extract of Rubus coreanus (0.05–0.2 mg/ml). In the histopathological specimen of Masson’s trichrome stain, areas of kidney interstitial fibrosis were attenuated in the treatment group (10.6 ± 1.3% area vs. 17.2 ± 2.3% area, P < 0.001). In the western blot analysis, protein abundance of α-SMA (12.9 ± 5.9 vs. 19.8 ± 3.1 fold changes compared to sham group, P = 0.046) significantly decreased in the treatment group. In the in vitro experiment, HK-2 cells treated with TGF-β and MN705 showed a dose-dependent significant decrease in the protein expression of fibronectin and phospho-Smad2/3 with increase of MnSOD. The extract of Rubus coreanus attenuates kidney fibrosis in the UUO mouse model and TGF-β-treated human kidney proximal tubular cells. TGF-β-related Smad and Smurf signaling pathways involved in the development of fibrosis are effectively inhibited through extract of Rubus coreanus and can be a potential target for prevention of kidney fibrosis.